Estudo fitoquímico de Hancornia speciosa Gomes : isolamento, determinação estrutural e atividade biológica - Sampaio, Taís Santos (2008)
This work deals with the phytochemical study of mangaba, Hancornia speciosa Gomes (Apocynaceae). The first chapter deals with the role of volatile compounds from leaves and fruits. The effect of drying time on the chemical compositions of volatile oils from leaves was investigated. Thus, it was possible to verify that there is a decrease in the abundance of alcohols such as (E)-3-hexenol (68.6% fresh leaves; 13.3% after 10 days of drying), while the percentage of oxygen-containing monoterpenes such as geraniol (2.4% fresh leaves; 54.7% after 10 days of drying) is increased. On the other hand, the effect of the stage of maturity on the volatile components of mangaba fruit was investigated at three different stages. The volatile analyses showed an obvious difference, both in qualitative and relative abundance, of major components, according to stage of maturity. Thus, it became apparent that fruits at the initial stage (immature) present oxygen-containing monoterpenes, such as (Z)-linalool oxide, (E)-linalool oxide and linalool in a higher relative percentage, while esters, alcohols, aldehydes and ketones were detected at low percentages. Nonetheless, esters, alcohols, aldehydes and ketones predominated in the fruits at the final stage (mature) while the percentage of oxygen-containing monoterpenes was very much reduced. Finally, the volatile profile of the fruits at the intermediate stage showed esters, alcohols, aldehydes and ketones like those found in mature fruits, but at an intermediate percentage. In the same way, there was an intermediate percentage of oxygen-containing monoterpenes as was also observed in higher amounts in immature fruits. The second chapter deals with isolation and structure elucidation of twelve compounds from the latex of fruits of H. speciosa: 3-β-O-hexadecanoyl lupeol, 3-β-O-(3 -hydroxyhexadecanoyl) lupeol, 3-β-O-(9-octadecenoyl) lupeol, 3-β-O-octadecanoyl lupeol, 3-β-O-(3 -hydroxyoctadecanoyl) lupeol, 3-β-O-(3 -hydroxyeicosanoyl) lupeol, 3-β-O-(3 -hydroxydocosanoyl) lupeol, 3-β-O-(3 ,5 -dihydroxyeicosanoyl) lupeol, α-amyin, β-amyrin, lupeol and sucrose octaacetate. For structure elucidation of these natural compounds IR, EM and NMR techniques (1H, 13C, DEPT) were used. Finally, in the last chapter the extracts and some fractions of H. speciosa were screened for their biological activities in vitro.